Analisis Kualitas Website E-Commerce Tokopedia Menggunakan Metode Webqual 4.0 dan Importance- Performance Analysis (IPA) - Kartika Gianina Tileng; Billy Agustian Dharmawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
A website becomes an important thing for an institution especially in education. A website may give picture of an educational institution. This attracts the author to do a research on a website. The objective of this study is to evaluate the quality of the website of the library of Ciputra University, Surabaya. WebQual 4.0 and the Importance-Performance Analysis (IPA) is used. The 50 respondents are users of the Library of the Ciputra University, which are students and lecturers. Data collection done by questionnaire which contains three variables: usability, information quality, and service interaction quality. They spread into 22 items of questions. The result shows that the evaluated website has 99.2% of the respondent are satisfied with the services. The gap level is 1.21 which shows that the performance of the evaluated website is bellow expectation. The quadrant analysis found two main attributes which are US5 (the website has an interesting display) and KL3 (the user feels safe about their personal data in the website).